A comparative analysis of high-intensity technique-specific intervals and short sprint interval training in taekwondo athletes: Effects on cardiorespiratory fitness and anaerobic power - Song, Y.; Sheykhlouvand, M. (Journal of Sports Science & Medicine, 2024)
Technique-specific high-intensity interval training (HIITTS) has been proven to be an effective method to enhance the sport-specific bio-motor abilities of taekwondo athletes. However, studies regarding its effects on comprehensive measures of cardiorespiratory fitness are limited. Furthermore, there is a lack of clarity regarding the extent of individual adaptations to this method compared to HIIT in the form of repeated sprints (HIITRS). This study compared the individual adaptations to HIITRS and HIITTS on cardiorespiratory fitness and anaerobic power in trained taekwondo athletes (age = 19.8 ± 1.3 years; body mass = 75.4 ± 9.1 kg; height = 1.73 ± 0.0 .m). All participants completed three sessions per week of a 60-minute regular taekwondo training. Following the 60-minute training, participants completed 3 sets of 10 × 4 s all-out HIITRS or same sets of repeated kicks with both legs (HIITTS) over a 6-week training period. In both groups, rest intervals were set at 15 seconds between efforts and one minute between sets. Before and after the training period, participants underwent a series of lab- and field-based tests to evaluate cardiorespiratory fitness and bio-motor abilities. Both interventions resulted in significant improvements in maximum oxygen uptake (VO2max), O2 pulse (V?O2/HR), first ventilatory threshold (VT1), second ventilatory threshold (VT2), cardiac output (Q?max), stroke volume (SV), peak power output (PPO), average power output (APO), squat jump (SJ), and countermovement jump (CMJ). However, linear speed (20-m speed time) and taekwondo-specific agility test (TSAT) only responded to HIITRS. HIITRS resulted in greater changes in VO2max, VO2/HR, VT2, and Q?max, and higher percentage of responders in measured parameters than HIITTS. In addition, HIITRS elicited lower inter-individual variability (CV) in percent changes from pre- to post-training in all measured variables. These results suggest that incorporating 3 sessions per week of HIITRS into regular taekwondo training results in significantly greater and more homogenized adaptations in cardiorespiratory fitness and bio-motor abilities than HIITTS among trained taekwondo athletes.